How gratitude and admiration differently enhance sustainable consumer behavior - Che, Cheng; Zhou, Miaomiao; Li, Suhui (Frontiers in Psychology, 2025)
Prior research indicates that various emotions linked to distinct values can result in unique consumer behaviors. The research is based on the discrete emotion theory, human value theory, and the theory of emotional-value consistency. It uses the experimental method to explore the influence of two completely different positive emotions, gratitude and admiration, on consumers’ willingness to engage in sustainable behaviors. It is based on the concepts of differentiated emotions, human values, and the congruence between emotions and values. The research demonstrates that personal values influence the effectiveness of demonstrations of gratitude and admiration. When self-transcendence values are prioritized, gratitude increases customers’ likelihood of engaging in sustainable behaviors; conversely, when self-enhancement values are emphasized, admiration heightens consumers’ motivation to act sustainably. Self-efficacy clarifies this concept. Two investigations validated these impacts, augmenting our comprehension of the factors influencing sustainable consumer behavior, which benefits both marketers and regulators.